2018
DOI: 10.1002/ange.201808385
|View full text |Cite
|
Sign up to set email alerts
|

Lead‐Free Solar Cells based on Tin Halide Perovskite Films with High Coverage and Improved Aggregation

Abstract: Tw osimple methods to improve tin halide perovskite film structure are introduced, aimed at increasing the power conversion efficiency of lead free perovskite solar cells.F irst, ah ot antisolvent treatment (HAT) was found to increase the film coverage and prevent electrical shunting in the photovoltaic device.Second, it was discoveredthat annealing under alow partial pressure of dimethyl sulfoxide vapor increased the average crystallite size. The topographical and electrical qualities of the perovskite films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 42 publications
(220 reference statements)
2
40
0
1
Order By: Relevance
“…1). This particular perovskite formula was selected for its optimal charge extraction when paired with common hole transport materials such as PEDOT:PSS 15,34 . Following the widely used method for tin perovskite film formation, 10 mol% SnF 2 was also added to the precursor solution containing SnI 2 , FAI, and MAI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). This particular perovskite formula was selected for its optimal charge extraction when paired with common hole transport materials such as PEDOT:PSS 15,34 . Following the widely used method for tin perovskite film formation, 10 mol% SnF 2 was also added to the precursor solution containing SnI 2 , FAI, and MAI.…”
Section: Resultsmentioning
confidence: 99%
“…SnF 2 is an additive which is important for the film growth control. The perovskite films were fabricated with our hot antisolvent treatment (HAT), which improves the film coverage 15 . No difference in the X-ray diffraction (XRD) patterns was observed for the films prepared from different SnI 2 sources ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] As the most promising alternative, Sn‐based perovskites outperform all of the currently reported Pb‐free perovskites in terms of photovoltaic performance. [ 6–13 ] In an Sn‐based perovskite material system, the all‐inorganic CsSnI 3 with native inorganic structural stability, favorable direct bandgap (1.3 eV), extra‐low exciton binding energy (18 meV), and excellent optical absorption coefficient (10 4 cm –1 comparable to that of MAPbI 3 ), is the most investigated Sn‐based semiconductor material for photovoltaic applications. [ 14–16 ] However, compared with hybrid MASnI 3 and FASnI 3 PSCs of a significant leap in PCE over 10%, the potential application of all‐inorganic CsSnI 3 PSCs seriously suffered from the limitation of a low PCE of only around 5%.…”
Section: Introductionmentioning
confidence: 99%
“…used preheated chlorobenzene as antisolvent to fabricate FA 0.75 MA 0.25 SnI 3 based perovskite film. [ 103 ] It has been observed that at elevated temperature the miscibility between antisolvent (chlorobenzene) and perovskite precursor solvent (DMSO) increases, which enhanced the efficiency of the antisolvent, i.e., faster nucleation rate. At optimum preheat temperature (65 °C), chlorobenzene performed best producing very dense, smooth perovskite film.…”
Section: Role Of Antisolvents To Improve the Perovskite Film Formationmentioning
confidence: 99%